Blood orange (Citrus sinensis) as a rich source of nutraceuticals: investigation of bioactive compounds in different parts of the fruit by HPLC-PDA/MS. Issue 22 (18th November 2021) - Russo, Marina; Bonaccorsi, Ivana Lidia; Arigò, Adriana; Cacciola, Francesco; De Gara, Laura; Dugo, Paola; Mondello, Luigi
Abstract: This study is part of a wider investigation aimed to sustain the economical value of the by-products generated by the Citrus industry. In particular, the protected geographic indication (PGI) red orange of sicily (known as blood orange) has been analysed by HPLC and by the enzymatic AOAC method. All the by-products contain significant amounts of biologically active compounds (limonoids and flavonoids). The decanted pulps were the most abundant, with the highest amount of flavonoids (130 g/kg) and high amount of limonoids (5.5 g/kg). Seeds were the best source of limonoids with about 10 g/kg. Low amount of anthocyanins were found only in coarse pulps and waste water. The total, the insoluble and the soluble dietary fibre (TDF, IDF and SDF respectively) were also determined. The pulps resulted to be the best source of dietary fibre, based on the amount and on the best insoluble/soluble ratio. Graphical Abstract: